Planetary Nebulae as Sources of Chemical Enrichment of the Galaxy - Kwok, Sun (Frontiers in Astronomy and Space Sciences, 2022)
During the late asymptotic giant branch (AGB) phase of stellar evolution, the element carbon is created through the triple-α nuclear reaction. This is followed by the synthesis of other heavy elements via neutron capture in the core and the dredge-up of these elements to the surface by convection. Simple molecules and solid-state minerals begin to form in the upper photosphere. These molecules and solids are ejected into the interstellar medium by a strong stellar wind. During the subsequent post-AGB evolution, complex organics with aromatic and aliphatic structures are synthesized in the circumstellar envelope. Planetary nebulae, formed by swept-up circumstellar material, are found to show strong spectral signatures of ions, atoms, molecules, and inorganic and organic solids. These ejected materials of planetary nebulae serve as primordial ingredients of formation of new stars and planetary systems. Stellar synthesized organic solids may survive their journeys through the interstellar medium and evidence for remnants of such organics can be found in our own Solar System. In this paper, we summarize the recent observations of circumstellar synthesis of molecules and solids and discuss the implications of these ejected circumstellar materials on the chemical enrichment of the Galaxy and planetary systems.